From adverse childhood experiences to wellbeing: Portfolios of resilience - Wekerle, Christine (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2020)
Resilience has always been present across human history, as we have contended with the wide array of adversities. Resilience research has gained significantly increasing momentum as a core principle of the trauma-informed approach to service. Resilience research supports not only targeting psychopathology symptom reduction, but also recognizing a portfolio of resilience components to harness in youth interventions. The present discussion considers the innovative research work of Hamby and colleagues (2020) in terms of their portfolio of resilience model and current evidence for a dual-factor model of social support (social support seeking and social support receiving). Social support is a frequent intervention component, particularly in developing help-seeking skills, within youth programming. Their findings support this factorial approach that considers the giving-receiving experience, and how the four categories of Interconnected, Rebuffed, Tended, and Isolated may relate to differing resilience profiles. This research raises important questions for future work in terms of the fit between seeking and receiving that places the youth centrally in this consideration. Youths’ journey from trauma to resilience in a way that validates their portfolio of resilience assets, strengths, and potential is central to a trauma-informed approach to youth well-being, as well as how we negotiate youth rights with our developmental, clinical and health responsibilities.